2020
DOI: 10.1111/liv.14360
|View full text |Cite
|
Sign up to set email alerts
|

The role of nutrition in non‐alcoholic fatty liver disease: Pathophysiology and management

Abstract: A healthy diet together with physical activity could induce weight loss and control the progression of non‐alcoholic fatty liver disease (NAFLD). However, the composition of diet has not been clearly established. Macronutrients such as saturated fatty acids (SFA), trans‐fats, simple sugars and animal proteins have a harmful effect on the liver. On the other hand, monounsaturated fats (MUFAs), polyunsaturated (PUFAs) omega‐3‐fats, plant‐based proteins and dietary fibres are considered to be beneficial to the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 29 publications
3
152
1
2
Order By: Relevance
“…Considering that diet has been described as a modulator in NAFLD progression and one of the multiple factors that could modify the gut microbiota, and consequently its derived metabolites [23,24], we analyzed the food frequency consumption data from the recruited volunteers. Although it is recommended that NAFLD patients follow a healthy diet [25], our results showed no differences regarding food intake. For this reason, diet was not a confounding factor to consider within our cohort and all the reported changes in metabolites concentration among groups are independent of dietary factors.…”
Section: Discussioncontrasting
confidence: 69%
“…Considering that diet has been described as a modulator in NAFLD progression and one of the multiple factors that could modify the gut microbiota, and consequently its derived metabolites [23,24], we analyzed the food frequency consumption data from the recruited volunteers. Although it is recommended that NAFLD patients follow a healthy diet [25], our results showed no differences regarding food intake. For this reason, diet was not a confounding factor to consider within our cohort and all the reported changes in metabolites concentration among groups are independent of dietary factors.…”
Section: Discussioncontrasting
confidence: 69%
“…In accordance with this view, moderate or vigorous physical activity were recently shown to reduce fat, inflammation and oxidative stress in the liver even in cases without any notable changes in BMI status [35]. Previous studies have shown that Western diet characterized by high fat, high carbohydrate and insufficient vitamin intake may provide triggers for insulin resistance and associated hepatotoxicity [14,46,[51][52][53][54][55][56]. On the other hand, adherence to a healthy diet has recently been emphasized among the first-line treatment options for NAFLD [52,57].…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that Western diet characterized by high fat, high carbohydrate and insufficient vitamin intake may provide triggers for insulin resistance and associated hepatotoxicity [14,46,[51][52][53][54][55][56]. On the other hand, adherence to a healthy diet has recently been emphasized among the first-line treatment options for NAFLD [52,57].…”
Section: Discussionmentioning
confidence: 99%